2015
DOI: 10.1136/archdischild-2014-307265
|View full text |Cite
|
Sign up to set email alerts
|

Associations between late and moderately preterm birth and smoking, alcohol, drug use and diet: a population-based case–cohort study

Abstract: ObjectiveThis study explores the associations between lifestyle factors and late and moderate preterm birth (LMPT: 32+0–36+6 weeks' gestation), a relatively under-researched group.Study designA population-based case–cohort study was undertaken involving 922 LMPT and 965 term (37+ weeks' gestation) singleton live and stillbirths born between 1 September 2009 and 31 December 2010 to women residing in Leicestershire and Nottinghamshire, UK. Poisson multivariable regression models were fitted to estimate relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
2
25
3
1
Order By: Relevance
“…Although other studies have suggested that diets containing high amounts of certain fruits and vegetables can reduce the risk for preterm birth (Myhre et al 2013; Smith et al 2015), our study showed that not consuming fruit daily only bordered in significance of being related to spontaneous birth, and not consuming vegetables daily showed no relationship at all. With the exception of alcohol and folic acid, all of the odds ratios of the more suboptimal health behaviour and psychological characteristics pointed in the direction of an increased risk for spontaneous preterm birth, although none of the odds were very high and none of the relationships significant.…”
Section: Discussioncontrasting
confidence: 95%
“…Although other studies have suggested that diets containing high amounts of certain fruits and vegetables can reduce the risk for preterm birth (Myhre et al 2013; Smith et al 2015), our study showed that not consuming fruit daily only bordered in significance of being related to spontaneous birth, and not consuming vegetables daily showed no relationship at all. With the exception of alcohol and folic acid, all of the odds ratios of the more suboptimal health behaviour and psychological characteristics pointed in the direction of an increased risk for spontaneous preterm birth, although none of the odds were very high and none of the relationships significant.…”
Section: Discussioncontrasting
confidence: 95%
“…[21] Another study conducted on 922 premature and 965 late birth mothers found that 38% of premature births were in females who smoked during pregnancy. [22] In this study, 21.7% of preterm delivery mothers quit smoking during gestation, 11.7% were occasional smokers, and 3.3% were smokers during pregnancy; 93.3% of term delivery mothers did not smoke at all. Regarding smoke exposure without smoking, it was found that preterm delivery mothers were generally exposed to cigarette smoke by their husband (70.7%), whereas 33.3% of term delivery mothers were exposed to cigarette smoke from outside (p<0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Maternal lifestyle (14) and health status, including diseases with onset prior to or during pregnancy (15), may influence oxidative stress and affect the apoptotic pathway leading to at-term birth or sPTB, both of which also appear consequent to a mechanism involving genetic and non-genetic factors, which may modulate the oxidative stress-induced apoptosis.…”
Section: Induction Of the Apoptotic Pathway By Oxidative Stress Inmentioning
confidence: 99%